1995
DOI: 10.1007/bf02914990
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary folliculo-stellate-like cells stimulate somatotropic pituitary tumor growth in nude mice

Abstract: A new cell line (TtT/GF) established from a murine pituitary thyrotropic tumor having characteristics similar to those of pituitary folliculo-stellate cell (FS cell) was implanted into nude mice together with cells from a rat pituitary somatotrophic tumor cell line (MtT/S) to determine whether the former enhances pituitary tumor growth. For as long as 2-3 mo after implantation, MtT/S cells implanted either alone or together with fibroblasts formed either no tumors or only very small tumors in the nude mice. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Here we demonstrate the participation of gp130 in auto-paracrine stimulation of in vivo MtT/S cell growth using as model the dependence of the somatotrophic MtT/S cell line on the folliculostellate TtT/GF cell line to induce tumour formation in nude mice (23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Here we demonstrate the participation of gp130 in auto-paracrine stimulation of in vivo MtT/S cell growth using as model the dependence of the somatotrophic MtT/S cell line on the folliculostellate TtT/GF cell line to induce tumour formation in nude mice (23).…”
Section: Discussionmentioning
confidence: 87%
“…These data provide evidence supporting a link between gp130 and pituitary abnormal growth. Participation of gp130 cytokines in pituitary gland tumorigenesis is further underlined by evidence indicating that the MtT/S somatotrophic cell line depends on the IL-6-and LIF-producing TtT/GF FS cell line to generate tumours in nude mice (23). Although the mechanism by which TtT/GF cells contribute to MtT/S cell tumorigenicity is not clear, one possible way might be through the liberation of cytokines and growth factors that stimulate MtT/S growth.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently it has been shown that VEGF is up-regulated in response to estrogen in as yet unidentified pituitary cells of Fischer 344 rats, indicating an early onset of angiogenesis during the development of estrogen-induced prolactinomas in these animals (Banerjee et al 1997). Furthermore, it has been reported that TtT/GF cells are essential for pituitary tumor formation in nude mice, probably by supporting angiogenesis (Koyama et al 1995). However, VEGF-producing FS cells are normally absent or rare within adenomas (Marin et al 1992, Ueta et al 1995, but it has been reported that a transition zone exists between the adenoma and the normal pituitary tissue that is extremely rich in FS cells (Marin et al 1992, Farnoud et al 1994.…”
Section: Figurementioning
confidence: 99%
“…IL-6 has been also reported to stimulate growth of rat tumor pituitary cells and of TtT/GF cells (27,28). Accordingly, the latter IL-6-producing cell line stimulates growth of somatotrophic tumor cells in nude mice (29). LIF released from primary bovine pituitary cultures can also suppress the proliferation of aortic endothelial cells and is therefore considered as a factor regulating pituitary angiogenesis (22).…”
Section: Pituitary Functions Of the Gp130 Cytokinesmentioning
confidence: 99%